Sustainable Crop Protection Through Improved Choices With Public And Private Extension (Agro-Science Letters, 2026)
Whether farmers benefit more from pest management guidance provided by  public agencies versus private entities affiliated with agrochemical companies  remains a critical question in agricultural policy. Transitioning toward more  sustainable farming depends fundamentally on the choices farmers make  regarding technology and production inputs, choices that are shaped by  access to information and peer learning. Advisory services are especially  valuable when new or complex technologies are involved, supplementing  knowledge gained through farmer-to-farmer exchange. Pest management  decisions, in particular, are frequently guided by extension services, making  these services central to contemporary agricultural policy debates. Global  trends indicate that pest pressure is intensifying—driven partly by climate  change and the growing commercialization of advisory services—while  societal concern over pesticide-related environmental and public health  risks continues to mount. Pesticide resistance is also emerging as a major  challenge. In this context, extension services carry significant responsibility,  as farmers’ pest management choices affect not only their own livelihoods  but also the wellbeing of surrounding communities and the broader public.  Consequently, extension guidance should be directed toward holistic  strategies that maximize collective welfare.
Keywords: Crop Protection; Extension; Insecticide; Herbicide; Weed Management